Technical notes on the endoscopic endonasal approach to the craniovertebral junction for odontoidectomy. Issue 2 (March 2018) - Tang, Dennis; Roxbury, Christopher; D'Anza, Brian; Kshettry, Varun; Woodard, Troy; Recinos, Pablo; Sindwani, Raj
Introduction: Odontoidectomy can help decompress ventral compression of the brainstem and upper cervical spinal cord in the presence of bony abnormalities of the craniovertebral junction (CVJ), e.g., an odontoid pannus. Endonasal approaches have been shown to be associated with lower morbidity compared with traditional transoral approaches. We demonstrated an entirely endonasal approach to the CVJ. Materials and Methods: We presented our technique for performing an endoscopic endonasal odontoidectomy. Results: The patient underwent an open posterior cervical spinal fusion to stabilize the CVJ due to destabilization that occurs with odontoidectomy either as part of a single procedure or in a staged manner, depending on the surgeon's preference. By using a two-surgeon, multihanded technique in collaboration with neurosurgery, the anterior CVJ was safely approached endoscopically through the nasopharynx. A midline incision was created and the soft tissue was lateralized widely. The first cervical vertebra (C1) arch was removed with a drill exposing the odontoid process and any associated pannus, which were then resected. Because this approach was entirely extradural, no reconstruction was necessary. Closure was accomplished by placing absorbable packing material in the defect and medializing the nasopharyngeal tissues. Conclusion: Endoscopic endonasal odontoidectomy offers excellent exposure and less morbidity than traditional transoral approaches. This technique should be considered in appropriately selected patients.